The Arbitral Tribunal’s Award on the Status of the Geographic Features in the South China Sea - Nitiruchirot, Yossapon (Nitipat NIDA Law Journal, 2021)
The South China Sea (SCS) has numerous geographic features. China has claimed all those features, while the Philippines has claimed some. There claims over the two countries has led to the territorial dispute between them. The dispute mechanism under the United Nations on the Law of the Sea Convention of 1982 (LOSC) constitutes a compulsory procedure, namely, a state party may file the case to a tribunal without consent of another party for the dispute concerning the interpretation or application of the LOSC. Therefore, it is not easy to apply this mechanism to solve the dispute between the two countries because the dispute between them is a territorial dispute which is not the dispute concerning the interpretation or application of the LOSC. Nevertheless, the Philippines is able to file China under this mechanism by using the technique of asking the tribunal to indicate the status of those features, not to indicate the owner over those features and after the tribunal render its award the sovereignty of China over those features will be unavoidably affected.